Overcoming: A Concept Analysis - Brush, Barbara L. (2011)
This article provides an operational definition of overcoming as a first step in the systematic analysis of the concept. Using the method described by Walker and Avant (2005), the authors identify the attributes and characteristics of overcoming and its theoretical and practical application to nursing. Sample cases from clinical research illustrate the concept further. Further nursing research needs to test the theoretical relationships between overcoming and outcome variables.